Doctor-Patient Communication in Tanzanian Public Hospitals: Language Use, Code-Switching, and Accommodation Strategies - MAKULILO, PRISCA BONIPHACE (Universitas Negeri Yogyakarta, 2025)
This study examined how language use and communication strategies influence doctor-patient interactions in Tanzanian public hospitals. Guided by Communication Accommodation Theory, the study focused on Amana, Mwananyamala, and Temeke Regional Referral Hospitals. Using a phenomenological qualitative design, data were collected through observations, interviews, and document reviews from 90 participants (30 doctors, 30 nurses, and 30 patients). Data were analyzed using NVivo 12 software, enabling thematic coding and sentiment analysis. Findings revealed that Swahili was the dominant language, but code-switching with English was common, particularly for technical terms. While simplification, analogies, non-verbal cues, and occasional third-party interpretation improved understanding, excessive or unexplained English terms led to confusion especially among elderly or less-educated patients. Cultural and linguistic mismatches further hindered communication when doctors failed to adapt to patients' backgrounds. The study recommends Swahili communication training, standardized bilingual materials, and integration of communication skills into medical education. These findings contribute to efforts toward linguistically inclusive and culturally responsive healthcare in Tanzania.